PENGARUH PENDIDIKAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI DINAS KETENAGAKERJAAN KOTA MEDAN - Sastra Sinaga, Deni; Sianturi, Eko suprianto; Sinaga, Agam; Hutabarat, Lamminar (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2023)
Based on the description of this research, it aims at education and career development, which are factors that can increase and decrease employee performance. and career development on employee performance at the Medan City Manpower Office. The formulation of this employee performance problem can be seen from the employee education that is not yet good and the career development that is implemented is not yet effective in agencies. Hypothesis This study aims to determine how much influence education and career development have on employee performance at the Medan City Manpower Office. Data collection methods used in this study were observation, interviews, and distribution of questionnaires. The population in the study consisted of 58 employees in the agency. Data analysis tools are multiple linear regression analysis, partial test (t), simultaneous test (F), adjustid R Squer test and determination test (R2). The conclusion of the education variable, results are obtained where the influence of education is significant 0.001> 0.05 and the value of tcount> ttable (2.961> 1.673), career development is obtained from the results where career development has a significant value of 0.001> 0.05 and the value of tcount> ttable (14.894> 1.673). simultaneously carried out on education and career development shows a value of tcount> ttable (371.338> 3.165) and a significant value of 0.000> 0.05. Furthermore, the R2 value is 0.929, which means that education and career development affect employee performance by 92.9%, while the remaining 7.1% is influenced by other factors. So it can be concluded that the independent variables (education and career development) together have a significant effect on the variable (employee performance) at the Medan City Manpower Office. Suggestions for agency leaders to have a schedule for consulting with employees so that employees are more focused in carrying out their duties and should be able to achieve predetermined work targets.